End-to-end verifiable cumulative voting without tallying authorities. (8th May 2023) - Bag, Samiran; Azad, Muhammad Ajmal; Hao, Feng
In this paper, we propose the first end-to-end (E2E) verifiable e-voting system for cumulative voting without requiring any tallying authorities. To our knowledge, none of the existing e-voting systems implemented for cumulative voting are end-to-end verifiable; if there is any bug or tampering at the tallying software, the tally would be inadvertently modified without any voter noticing this. Although there are existing voting systems (e.g., mix-net-based) that could be adapted to support cumulative voting with E2E verifiability, they generally require a set of tallying authorities, which can lead to substantial complexity of finding and managing such authorities in practice. We address this issue by adopting novel cryptographic techniques to achieve E2E verifiability for cumulative voting, but without involving any tallying authorities. We formally define a model to prove the security of our system, and present the efficiency analysis to show that our proposed solution is feasible for practical use.